2016
DOI: 10.1016/j.neuron.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Self-Other Mergence in the Frontal Cortex during Cooperation and Competition

Abstract: SummaryTo survive, humans must estimate their own ability and the abilities of others. We found that, although people estimated their abilities on the basis of their own performance in a rational manner, their estimates of themselves were partly merged with the performance of others. Reciprocally, their ability estimates for others also reflected their own, as well as the others’, performance. Self-other mergence operated in a context-dependent manner: interacting with high or low performers, respectively, enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
171
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(185 citation statements)
references
References 44 publications
12
171
0
2
Order By: Relevance
“…Our results, therefore, align with several strands of research that have implicated a similar ventral region of the MPFC in the representation and processing of self-relevant information (Adolphs, 2009, Denny et al., 2012, Jenkins et al., 2008, Kelley et al., 2002, Kumaran and Maguire, 2005, Macrae et al., 2004, Mitchell et al., 2005, Mitchell et al., 2006, Mobbs et al., 2009, Ochsner et al., 2004, Tamir and Mitchell, 2011, Tamir and Mitchell, 2012, Wittmann et al., 2016). This evidence has come from a range of studies: experiments in which participants are asked to judge the applicability of traits to themselves compared with others (Denny et al., 2012, Kelley et al., 2002, Mitchell et al., 2006), work suggesting that items subjected to self-related processing are afforded privileged status in memory (Macrae et al., 2004), and research on constructing imagined scenarios involving either oneself or others (De Brigard et al., 2015, FeldmanHall et al., 2012, Hassabis et al., 2014, Schacter and Addis, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our results, therefore, align with several strands of research that have implicated a similar ventral region of the MPFC in the representation and processing of self-relevant information (Adolphs, 2009, Denny et al., 2012, Jenkins et al., 2008, Kelley et al., 2002, Kumaran and Maguire, 2005, Macrae et al., 2004, Mitchell et al., 2005, Mitchell et al., 2006, Mobbs et al., 2009, Ochsner et al., 2004, Tamir and Mitchell, 2011, Tamir and Mitchell, 2012, Wittmann et al., 2016). This evidence has come from a range of studies: experiments in which participants are asked to judge the applicability of traits to themselves compared with others (Denny et al., 2012, Kelley et al., 2002, Mitchell et al., 2006), work suggesting that items subjected to self-related processing are afforded privileged status in memory (Macrae et al., 2004), and research on constructing imagined scenarios involving either oneself or others (De Brigard et al., 2015, FeldmanHall et al., 2012, Hassabis et al., 2014, Schacter and Addis, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the latter function comes from a recent study which showed that pgACC activity tracks a running average of subjects' performance history and predicts subjects' explicit evaluations of recent performance (30). Unlike our study in which performance was designed to be independent from one trial to another, performance was rigged such that it was auto-correlated across trials and thus could only be learnt from trial-by-trial feedback.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%
“…This raises the possibility that activity in response to others in this region may become more similar to self when interacting with ingroup members, and that this mergence is greater when an individual is highly fused to the group. Indeed, recent work has suggested that representation of self and other during reward‐related interactions may merge within areas 32 and 9 in the MPFC, particularly overlapping with the regions that were differentially engaged by fusion to a group in this study (Wittmann et al., 2016). Here, rather than mergence depending on the actions of the other person, we show that VMPFC responses are also influenced by one's fusion to a social group .…”
Section: Discussionmentioning
confidence: 99%